Development of a Hydroponic System using an Atmega 2560 Microcontroller with Automatic Nutrition and pH Settings for Lettuce Cultivation - Susanti, Hera; Zaenurrohman; Riyadi Purwanto (Politeknik Piksi Ganesha Indonesia, 2023)
Hydroponic system is a technique of cultivating plants without using soil as a growing medium, but using water that is given nutrients and oxygen as a growing medium. Cultivation with hydroponic techniques must be able to pay attention and control nutrients, water content, and water ph. This research aims to create a lettuce cultivation system with intelligent hydroponic techniques using the ATmega2560 microcontroller. This system uses Arduino Mega as the control center, TDS sensor to monitor nutrition, PH sensor to monitor water acidity, and ultrasonic sensor to monitor water level. The optimal growth characteristic of lettuce is that the acidity level must be at pH 5.5-6.5 with the nutrients provided at 685-950 ppm. This system can help lettuce cultivation with hydroponic techniques by monitoring and controlling nutrients, pH, and water content in cultivated plants in real time to optimize lettuce growth.